KEBIJAKAN FORMULASI KORPORASI PENYELANGGARA APLIKASI PINJAMAN ONLINE ILEGAL SEBAGAI SUBJEK PIDANA - Dyah Dewi Alifia Rachma (Fakultas Hukum Universitas Tarumanagara, 2021)
Fintech Peer-To-Peer Lending is an information technology-based lending and borrowing service that is supervised by the OJK. But over time, illegal Fintech companies emerged that did not have permission from the OJK, causing new problems. These illegal fintechs commit crimes in terms of billing, such as making threats by distributing personal data. Meanwhile, in addition to that, there is no specific law that regulates Fintech, so in this case there is a need for a formulation policy related to corporations providing illegal online loan applications as an effort to overcome crime committed by corporations. The reorientation and reformulation of corporations that administer illegal online loan applications as criminal subjects shall at least include the following provisions: 1) When can a corporation that administers online loan applications be said to be criminal acts committed by the company; 2) Who is Criminally Responsible for Crimes Committed by Corporations Organizing Illegal Online Loan Applications; 3) Types of Sanctions Appropriate to Corporations Organizing Illegal Online Loan Applications as Criminal Subjects